Influence of Farming Background on the Educational Performance of Ordinary Level Students: Evidence from Northern Sri Lanka - Umashankar, K.; Jena, S. (Sri Lanka Agricultural Economics Association, 2011)
This research attempts to quantify the effect of the farming background on the educational performance of ordinary level students belonging to the rural farming community in the Jaffna district situated in the northern part of Sri Lanka. Purposive random sampling technique was used to pick the sample. The sample constituted a total of 287 respondents. A pretested structured questionnaire was administered to elicit the information from the respondents. After performing the regression diagnostic tests the collected data were analyzed within a framework of multiple regression analyses by employing the statistical software STATA 10. The results revealed that individual studying hours positively contributed to increasing the average marks of all the subjects at the significant level of 1%. This implies that when the students' individual average studying time increases by one hour the marks scored in Mathematics, Science, Tamil, English, and Cumulative average increased by 6.69, 4.53, 4.24, 3.96, 4.59 respectively. The student's age was also significant at 5% level and exerted a negative impact on the outcome in Mathematics. This implies that one-year increase in the age of student decreases the average marks of mathematics by 6.76. The paternal age factor also demands increased labor contribution from the children. When the fathers' age increases by one year, it reduces the student's overall performance by 4.74 at 10% significance level. Moreover the researchers found that if the progeny of the farming community is a male, the performance in English reduces by 6.61 at 5% significant level and the cumulative performance lessens by 3.54 points at 10% significant level. Finally this research concludes that increasing the student's individual studying hours and providing adequate facilities at home are more critical in improving the weighted average marks of the students
Keywords: Farming community; Educational performance; Multiple regression